PENERAPAN PENCATATAN BUKU KAS DIGITAL PADA UMKM KERUPUK BU MITRO KELURAHAN TANJUNGPINANG BARAT - Satria, Hendy; Zahiriyan, Zahiriyan; Peramana, Deppy (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to analyze more deeply regarding the application of digital cash books to MSMEs. The digital cash book used is the BukuKas application which can be accessed via an Android phone and downloaded from the playstore. This service was carried out for Bu Mitro's Kerupuk UMKM which is located on Jalan H. Agus Salim, West Tanjungpinang Village, West Tanjungpinang District, Tanjungpinang City. By using the BukuKas application, it is hoped that it will make it easier for Kerupuk Bu Mitro's MSMEs to know their financial management so that these MSMEs are able to continue to survive even during this difficult pandemic. This community service activity yielded the result that recording a digital cash book with the BukuKas application was very easy to implement and useful in helping Kerupuk Bu Mitro's UMKM in managing their finances